Social Action as a Culturally Situated Intersubjective Project (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
In this article we analyze the concept of social action, rescuing some sociophenomenological and hermeneutic contributions that allow us to re-describe this concept and, through it, advance in the intercultural opening of the human sciences. Thus, we articulate the concepts of sense of the action (Schütz, 2003), and of experiential meaning (Taylor, 2005) to enhance the contextual-cultural conditions that constitute to all action and that allow their understanding. We propose to overcome the mechanistic analysis of any human action through re-description as a culturally situated intersubjective project, whose configuration allows us to understand that the actions of Others and Ours are expressions of a meaningful whole, which is always concrete and diverse.
Keywords: Sense of the action; experiential meaning; intersubjective world of culture; contrast; expressivenes